2020
DOI: 10.1111/jfpp.14484
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted extraction of bioactive compounds fromAraucaria angustifoliabracts followed by encapsulation

Abstract: The aqueous extract of Araucaria angustifolia bracts was obtained by microwave‐assisted extraction and encapsulated by spray‐drying and freeze‐drying using pectin/hydrolyzed collagen (PEC‐HC) and polydextrose/partially hydrolyzed guar gum (PD‐PHGG) dispersions, added to the extract in the proportions of 0.25:0.75:9 and 0.5:0.5:9 (wt/wt/wt), respectively. The powders encapsulated with the PD‐PHGG mixture by spray‐drying and freeze‐drying showed the highest retention rates for total phenolic compounds (80.57% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…The findings clearly indicated that combining microwave and ultrasound technologies aided recovery of food components whilst reducing energy consumption. Dorneles & Noreña (2020) also used microwave technology, but this time as extraction aids for phenolic compounds to aid effective recovery in a more environmentally friendly process. Other researchers have investigated the role of non‐thermal technologies in extraction of bioactive ingredients and food preservation techniques to ensure the safety and quality of foods (Ali et al ., 2021).…”
Section: The Opportunities Of Novel Processing Technologiesmentioning
confidence: 99%
“…The findings clearly indicated that combining microwave and ultrasound technologies aided recovery of food components whilst reducing energy consumption. Dorneles & Noreña (2020) also used microwave technology, but this time as extraction aids for phenolic compounds to aid effective recovery in a more environmentally friendly process. Other researchers have investigated the role of non‐thermal technologies in extraction of bioactive ingredients and food preservation techniques to ensure the safety and quality of foods (Ali et al ., 2021).…”
Section: The Opportunities Of Novel Processing Technologiesmentioning
confidence: 99%
“…In this sense, biopolymers are preferred because of their physicochemical characteristics and biocompatibility with the human body, including polysaccharides, proteins, whey protein, and mucilage from different sources. 5,44,47,48 Nanotechnology involves various strategies using different materials at nanoscale dimensions to fabricate devices widely employed in the electronic and food industries, as well as in the pharmaceutical and biomedical fields. Nano-carrier systems have shown many advantages in the encapsulation of phenolic compounds, such as uniform morphology, high encapsulation efficiency, increased solubility, thermal and storage stability, as well as improved bioactivity.…”
Section: Main Challenges To Using Phenolic Compounds As Functional Ingredientsmentioning
confidence: 99%
“…Likewise, various wall materials can be used to protect these bioactive components and control their release at the target site. In this sense, biopolymers are preferred because of their physicochemical characteristics and biocompatibility with the human body, including polysaccharides, proteins, whey protein, and mucilage from different sources 5,44,47,48 …”
Section: Main Challenges To Using Phenolic Compounds As Functional In...mentioning
confidence: 99%
“…The encapsulation of pinhão extracts has been proposed by a few authors as follows. Dorneles and Noreña (2020) used hydrolyzed pectin/collagen and partially hydrolyzed polydextrose/ guar gum as encapsulating agents. The authors obtained microparticles by spray-drying and also by lyophilization, resulting in improved stability of antioxidant capacity during storage.…”
Section: Introductionmentioning
confidence: 99%